Effect of Fertilizer on The Growth and Yield of Jhum Crop under the Slush-mulch Condition for Sustainable Crop Production in the Chittagong Hill Tracts (Chts) of Bangladesh - Zonayet, Md.; Paul, Alok Kumar (International Journal of Bio-resource and Stress Management, 2020)
The purpose of this study was to evaluate the effect of fertilizer on the growth and yield of jhum crop under the Slush-mulch condition for sustainable crop production in Chittagong hill tracts (CHT) of Bangladesh. The experiments were conducted during March 2015 to February 2016 at Bandarban in Chittagong under the AEZ 29 (Northern and Eastern Hills Tract). The experiment was designed on Randomized Completely Block Design (RCBD) with three replications. Experiment had three treatments as T1 Control T2 Application of 100% chemical fertilizers on STB (N37 P15 K14 S8 kg ha-1) and T3 Application of 125% chemical fertilizers on STB along with mulch (about 50 kg natural weed per 20 m2 plot) and no mulch conditions. Fertilization under slush-mulch condition had a positive role on the yield of Jhum rice and that of other Jhum crops. Under sole application of fertilizer, the highest grain yield of rice (4.27 t ha-1) was obtained from the application of 125% of RDF on STB, the lowest value (2.65 t ha-1) being noted in control. On the other hand, mulching favored the yield of rice grain, the highest grain yield (4.44 t ha-1) being obtained from the combination of mulching along with the application of fertilizers @ 125% RDF on STB, the lowest grain yield (1.89 t ha-1) was recorded from the absolute control. The yield of jhum other crops also significantly influenced in mulch condition. The negative balance of soil nutrient was increased with the rates of fertilizer application under both mulch and no-mulch conditions.